ENHANCING STUDENT’S TECHNICAL VOCABULARY SIZE BY USING FRAYER MODEL GRAPHIC ORGANIZER - Meylina Meylina (ELP (Journal of English Language Pedagogy), 2020)
English vocabulary seems to be a crucial problem experienced by non-native students in STMIK Jayanusa Padang. Their low vocabulary knowledge caused several problems in understanding a text especially related to technical vocabulary. The purpose of this research was to improve the students' technical vocabulary size of the third-semester students at STMIK Jayanusa Padang through the Frayer model graphic organizer. This research used classroom action research. The data was collected through tests, field notes, and interviews. The findings of this research revealed that there was an improvement in students' technical vocabulary size obtained from the pretest, cycle 1 to cycle 2. The average score of the pretest was very low, 0.4. Then, it gradually improved in cycle 1 became 0.83 with an increasing point was 0.43 points. Next, the average score found in cycle 1 then better improved in cycle 2 which turned into 1.43 with the increasing point from cycle 1 to cycle 2 was 0.6 points. Shortly, Frayer Model influenced the enrichment of students' technical vocabulary size.